Experimental and numerical investigation of the strain response of the filament wound pressure vessels subjected to pressurization test. Issue 11 (23rd May 2019) - Bai, Hui; Yang, Bin; Hui, Hu; Yang, Yuqing; Yu, Qingwei; Zhou, Zhongqiang; Xian, Pingping
Abstract: This article presents the strain response of glass fiber reinforced epoxy matrix pressure vessels subjected to pressurization test. Three filament wound composite pressure vessels with different dimensions are manufactured by fiber winding processing, and the pressurization tests of these pressure vessels are performed. The stain of the inner/outer surface of the vessels during the pressurization tests is recorded. A progressive damage model is built based on the 3D Hashin failure criteria by finite element method (FEM) to predict the strain response of the composite pressure vessels. Fundamental mechanical tests that including the tensile, double cantilever beam, and three‐point end notched flexure tests of the composite laminates are carried out to determine the strength and stiffness parameters used in the FEM. The results show that the circumferential strain of the three composite pressure vessels is greater than the longitudinal strain. The maximum stress and strain occurs at the head of the pressure vessels. The predictions of FEM match the experimental results well, and the strain differences between FEM and experiments of the pressure vessels are less than 12%.